Christians, Primates, Friction Drums and Carnival Masks: Defamiliarisation in Carlo Levi's Cristo si è fermato a Eboli - Lampugnani, Raffaele (Spunti e Ricerche, 2016)
Cristo si è fermato a Eboli is Carlo Levi's autobiographical account of his internment by Fascist authorities to the remote southern Italian towns of Grassano and Aliano from 1935 to 1936. The book was received with enthusiasm and established the author as a leading novelist, intellectual and visual artist, but, above all, brought attention to the backward and culturally different Italian region of Lucania (now Basilicata), considered the "epitome" of southern Italian culture. As Levi himself states at the outset, the book describes the discovery of a different world, another civilisation closed-in within itself, within its customs and anguish, a motionless, distant and distinct civilisation. But Carlo Levi's sketches of people, customs, beliefs and landscapes de-familiarise the elements represented, bringing this civilisation within the realm of myth and mystery. It is argued that the strategy of de-familiarisation is aimed at emphasising cultural differences, suggesting a strong link between the contemporary southern Italian civilisation and previous classical societies or pre-Christian, or pre-historical archaic cultures - Levi's strategy of de-familiarisation supports his argument for regional autonomy based on the need to recognise major regional cultural and historical differences that are exacerbated by the insensitive mismanagement imposed by a centralised government.